Analysis of Numeracy Literacy Skills Of Students On The Pythagorean Theorem Material in Class VIII UPT SMP Negeri 7 Medan T.A. 2021/2022 - Adi Suarman Situmorang; Dahlia Fortuna Sinaga (CV. AFDIFAL MAJU BERKAH, 2022)
This research aims to determine the numeracy literacy ability of students in class VIII SMP Negeri 7 Medan. This type of research is descriptive qualitative research. The research was carried out in the even semester of the 2021/2022 academic year. The samples taken in this study using purposive sampling were students at UPT SMP Negeri 7 Medan, namely class VIII. The instrument used in this study was a numeracy literacy test in the form of 5 essay questions. Data collection techniques using triangulation techniques, followed by data analysis which includes data collection, data reduction, data presentation, and conclusions. Based on the objectives of the research results that have been made by researchers, it can be seen that there is a difference in the students' numeracy literacy skills in solving post-test test questions, which 50% of students' numeracy literacy skills are obtained at a high level, while 30% of students who have moderate level of numeracy literacy, and 20% of students who have low level of numeracy literacy. From numeracy literacy skills in the high-level category, it can be seen that students are able to solve problems that occur in everyday life.